Power Relation: Gaya Bahasa Penggambaran Kekuasaan - indriani triandjojo (Universitas Aki, 2014)
Language as a means of communication is used as a means of message exchange between the sender and the receiver. Information conveyed through words or text of an ad can involve feelings, emotions and cultural values. They all establish a communication process which has an important power as a marketing tool in the form of information that is persuasive. Language has a power and with it language is used by producer, ad makers or sender, to interact with its readers or receivers. This communication shows power relation between producer and consumer. Power relation is constructed so that the sender can position himself as desired. He, the owner of the power, can make his position higher, equal or lower than the consumer’s. Language as a means of communication can be used as a tool to build the power. Key words: Language, ad, communication, power, sender, receiver.